METASTATIC CUTANEOUS PLASMOCYTOMA IN A PATIENT LINEAR MORPHEA AND GENITAL LICHEN SCLEROSUS – AN ASSOCIATION TO KEEP IN MIND - Pereira, Neide; Cabral, Rita; Gonçalo, Margarida (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Background: Coexistence of lichen sclerosus and morphea, in most cases with extragenital localization, has been reported in the literature. Case report: A 58-year-old woman presented in 1998 with sclerotic and atrophic linear plaques on the right hemibody, whose histopathological study was compatible with linear morphea. Nine years later, on the residual atrophic areas, small whitish lesions grouped into plaques developed and histology was compatible with lichen sclerosus. Simultaneou- sly, ill-defined, pearly white plaques occurred in the vulva conditioning atrophy of the labia minora, compatible also on histology with genital lichen sclerosus (GLS). A good response to topical corticosteroids was observed. Discussion: In a recent study 38% of patients with morphea also suffer from GLS, suggesting that the two diseases may have common mechanisms or that GLS represents the genital manifestation of morphea. We emphasize the need to examine the genitalia of patients with morphea due to morbidity and the risk of squamous cell carcinoma associated with GLS. KEYWORDS – Genital diseases; Female; Lichen sclerosus et atrophicus; Scleroderma, localized; Skin diseases.